Mindfulness meditation regulates anterior insula activity during empathy for social pain. Issue 8 (15th May 2017) - Laneri, Davide; Krach, Sören; Paulus, Frieder M; Kanske, Philipp; Schuster, Verena; Sommer, Jens; Müller‐Pinzler, Laura
Abstract: Mindfulness has been shown to reduce stress, promote health, and well‐being, as well as to increase compassionate behavior toward others. It reduces distress to one's own painful experiences, going along with altered neural responses, by enhancing self‐regulatory processes and decreasing emotional reactivity. In order to investigate if mindfulness similarly reduces distress and neural activations associated with empathy for others' socially painful experiences, which might in the following more strongly motivate prosocial behavior, the present study compared trait, and state effects of long‐term mindfulness meditation (LTM) practice. To do so we acquired behavioral data and neural activity measures using functional magnetic resonance imaging (fMRI) during an empathy for social pain task while manipulating the meditation state between two groups of LTM practitioners that were matched with a control group. The results show increased activations of the anterior insula (AI) and anterior cingulate cortex (ACC) as well as the medial prefrontal cortex and temporal pole when sharing others' social suffering, both in LTM practitioners and controls. However, in LTM practitioners, who practiced mindfulness meditation just prior to observing others' social pain, left AI activation was lower and the strength of AI activation following the mindfulness meditation was negatively associated with trait compassion in LTM practitioners. The findings suggest that current mindfulness meditation could provide an adaptive mechanism in coping with distress due to the empathic sharing of others' suffering, thereby possibly enabling compassionate behavior. Hum Brain Mapp 38:4034–4046, 2017 . © 2017 Wiley Periodicals, Inc.